NILAI-NILAI PENDIDIKAN DALAM SURAT LUQMAN - Mukodi, Mukodi (IAIN Walisongo Semarang, 2011)
Abstract Â The result of this studyâlibrary researchâshowed that the values of Islamic education are contained in the Holy Qurâan surah Luqman verses 12-19. There are at least three basic education, namely aqidah education, syariâah education and character education. Aqidah education, there are two things: (1) prohibition of associating partners with Allah. Luqman al-Hakim himself had to prioritize monotheism education (tauhid) to his children, (2) believe in the place of hereafter. Luqman ordered his children to believe the reward of all his deeds. Especially retaliation for our gratitude to Him for every blessing and our sense of respect for both parents. Syariâah Education, there are two things, namely a command set up prayer and amar maârÅ«f nahy munkar. Character education, which is the command to ingratitude towards Allah SWT. For all the blessings and grace of God, we should be grateful to Him. *** Artikel ini merupakan penelitian kepustakaan. Penelitian menunjukkan bahwa pendidikan Islam termuat dalam al-Qurâan Surat Lukman 12-19. Setidaknya ada tiga tingkatan yaitu pendidikan aqidah, pendidikan syariâah, dan pendidikan karakter. Pendidikan aqidah meliputi dua hal: (1) larangan mensekutukan Allah. Lukman Hakim memprioritaskan pendidikan tauhid kepada anak-anak; (2)mempercayai hari akhir. Lukman Hakim mengajarkan kepada anak-anaknya untuk mempercayai balasan atas perbuatan yang dilakukan di dunia. Pendidikan syariah meliputi dua hal, yaitu mendirikan sholat dan amar maârÅ«f nahy munkar. Pendidikan karakter meliputi perintah untuk bersyukur kepada Allah atas semua karunia-Nya. Â Keywords: Luqman al-Hakim, pendidikan aqidah, pendidikan syariah dan pendidikan akhlak